2018
DOI: 10.1039/c7fo01849e
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the bitterness of pea and potato proteins by a complex coacervation method

Abstract: The incorporation of novel plant-based proteins into foods is often challenging due to an unacceptable bitter sensation. Typically, a combination of electrostatic and hydrophobic forces contributes to the proteins' bitterness. The current study therefore focuses on the development of electrical properties on cationic plant proteins to reduce their overall bitterness in order to improve the perceived sensorial acceptance. As such, we utilized a simple mixing process to induce complex coacervation of oppositely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Additionally, WPI and PP had a slightly higher protein content that could have contributed to this difference. Most likely, the bitter taste of WPI and PP are the reason that these bars required additional sweetener to reach iso-sweetness (Liu et al, 2014;Zeeb et al, 2018). It is important to note, for sugar reduction efforts, that within a single specific formulation it cannot be assumed that changing the protein type does not change the iso-sweet taste.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, WPI and PP had a slightly higher protein content that could have contributed to this difference. Most likely, the bitter taste of WPI and PP are the reason that these bars required additional sweetener to reach iso-sweetness (Liu et al, 2014;Zeeb et al, 2018). It is important to note, for sugar reduction efforts, that within a single specific formulation it cannot be assumed that changing the protein type does not change the iso-sweet taste.…”
Section: Discussionmentioning
confidence: 99%
“…The peptidase preparations were analyzed by sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis (SDS‐PAGE; 12.5%), as described previously . The protein bands of the SDS gel were stained with Coomassie Brilliant Blue R‐250.…”
Section: Methodsmentioning
confidence: 99%
“…10,12 Sodium dodecyl sulfate polyacrylamide gel electrophoresis The peptidase preparations were analyzed by sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis (SDS-PAGE; 12.5%), as described previously. 21 The protein bands of the SDS gel were stained with Coomassie Brilliant Blue R-250. The protein load (5 μg per lane) was determined by using the Bradford method 22 and bovine serum albumin as a reference.…”
Section: Determination Of the Process Stabilitymentioning
confidence: 99%
“…This result contrasted with high bitterness ratings of potato protein at pH 3, which were significantly higher ( P ≤ 0.05) compared to WSPE from C. protothecoides . Other researchers have found similar high bitterness ratings in potato protein and as well for other plant proteins such as pea and soy protein but the present study suggests that only a low bitter taste is observed in the WSPE of C. protothecoides . However, clearly more research is necessary to reveal more in‐depth sensory properties with a trained panel.…”
Section: Resultsmentioning
confidence: 99%